2016
DOI: 10.1007/s11356-016-8328-z
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study on toxicity of ZnO and TiO2 nanoparticles on Artemia salina: effect of pre-UV-A and visible light irradiation

Abstract: This study evaluated the toxicity potential of ZnO and TiO nanoparticles under pre-UV-A irradiation and visible light condition on Artemia salina. The nanoparticle suspension was prepared in seawater medium and exposed under pre-UV-A (0.23 mW/cm) and visible light (0.18 mW/cm) conditions. The aggregation profiles of both nanoparticles (NPs) and dissolution of ZnO NPs under both irradiation conditions at various kinetic intervals (1, 24, 48 h) were studied. The 48-h LC values were found to be 27.62 and 71.63 mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 62 publications
2
15
0
Order By: Relevance
“…The increase in starch grains and the production of larger grains has been reported in algae and higher aquatic plants after exposure to various ENMs [94,95]. Several authors reported increased lipid bodies and starch grains mainly occur under oxidative stress conditions [96][97][98], a toxicity mechanism commonly reported in nanotoxicity [99,100]. in algae and higher aquatic plants after exposure to various ENMs [94,95].…”
Section: Sunscreen Pr-enms Interaction With Biota 231 Interaction With P Subcapitatamentioning
confidence: 88%
See 1 more Smart Citation
“…The increase in starch grains and the production of larger grains has been reported in algae and higher aquatic plants after exposure to various ENMs [94,95]. Several authors reported increased lipid bodies and starch grains mainly occur under oxidative stress conditions [96][97][98], a toxicity mechanism commonly reported in nanotoxicity [99,100]. in algae and higher aquatic plants after exposure to various ENMs [94,95].…”
Section: Sunscreen Pr-enms Interaction With Biota 231 Interaction With P Subcapitatamentioning
confidence: 88%
“…in algae and higher aquatic plants after exposure to various ENMs [94,95]. Several authors reported increased lipid bodies and starch grains mainly occur under oxidative stress conditions [96][97][98], a toxicity mechanism commonly reported in nanotoxicity [99,100]. Similar to SUN1, SUN2-3 PR-ENMs were also not internalised but were adsorbed on the cell walls.…”
Section: Sunscreen Pr-enms Interaction With Biota 231 Interaction With P Subcapitatamentioning
confidence: 96%
“…In addition to organic filters, nanoparticles of both TiO 2 and ZnO have also been shown to have toxic effects on marine microalgae and zooplankton. [45][46][47][48] Although further studies are required on a wider diversity of species, these findings indicate that some UV filters have toxic effects on organisms at the bottom of the marine food web, with any alterations in these populations having potentially damaging consequences on organisms at higher trophic levels. 44…”
Section: Impact Of Uv Filters On Marine Organisms and Ecosystemsmentioning
confidence: 94%
“…Comparing light/dark exposures have, e.g., found illumination to influence sublethal effects of TiO 2 NM on fish, [ 83 ] as well as increased uptake and toxicity of ZnO and TiO 2 in brine shrimp. [ 84 ] These abiotic factors may not lead to the generation of NM functional fate groups directly, yet their role has to be considered when investigating the environmental fate and effect of NM. iii)Preaging of pristine NMs water, sediment or soil. …”
Section: Assessing How Transformations Impact On Bioaccumulation and mentioning
confidence: 99%